Textografia de uma comunidade de prática da Medicina Veterinária - Amanda Petry Radünz; Patrícia Marcuzzo (Revista Odisséia, 2022)
The process of internationalization of higher education institutions includes the development of academic practices in English language, regarded as the lingua francaof science (HÜLMBAUER et al., 2008; SWALES, 2018, p. 242), to facilitate the dialogue among institutions from different countries. The present study investigates a research group from the Veterinary Medicine field of a Brazilian higher education institution that publishes most of its research in English language. The study uses textography’s theoretical and methodological assumptions (SWALES, 1998a, 1998b, 2018) to analyze, textual and contextually, English language academic writing practices in the referred group, and it intends, ultimately, to contribute to the participants in this writing process. Up to this moment, a pilot survey was answered by10 participants, providing a first contact with the research group and with their academic writing practices in English language.